ANALISIS FINANSIAL USAHATANI KEDELAI DAN NILAI TAMBAH TAHU DI KABUPATEN LOMBOK TENGAH - Shafina Nabilah; Lukman Mohammad Baga; Netti Tinaprilla (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2015)
The  objectives  of  this  research  are  to  analyze  the  financial  of  soybean farmingand  count  the  number  of  value  added  processing  tofu  in  Central  Lombok Regency.  The  research  was  conducted  in  Pujut  Sub-district  in  Central  Lombok  and taken  30  farmers  as  the  sample.  The  sample  are  soybean  farmer  which  selected  by purposive  sampling.  The  result  showed  that  soybean  farming  is  feasible  to  develop because  R/C  >  1.  The  ratio  of  value  added  tofu  is  44.8  percent  of  the  production value.